Systematic Analysis of Cotton Non-specific Lipid Transfer Protein Family Revealed a Special Group That Is Involved in Fiber Elongation - Meng, Chengsheng; Yan, Yuanyuan; Liu, Zhengwen; Chen, Liting; Zhang, Yan; Li, Xiuxin; Wu, Liqiang; Zhang, Guiyin; Wang, Xingfen; Ma, Zhiying (Frontiers in Plant Science, 2018)
Non-specific lipid transfer proteins (nsLTPs) had been previously isolated from cotton fiber but their functions were unclear so far. Bioinformatic analysis of the tetraploid cotton genome database identified 138 nsLTP genes, falling into the 11 groups as reported previously. Different from Arabidopsis, cacao, and other crops, cotton type XI genes were considerably expanded and diverged earlier on chromosome At11, Dt11, and Dt08. Corresponding to the type XI genes, the type XI proteins (GhLtpXIs) all contained an extra N-terminal cap resulting in larger molecular weight. The research revealed that the expression of type XI genes was dramatically increased in fibers of tetraploid cotton compared with the two diploid progenitors. High-level of GhLtpXIs expression was observed in long-fibered cotton cultivars during fiber elongation. Ectopic expression of GhLtpXIs in Arabidopsis significantly enhanced trichome length, suggesting that GhLtpXIs promoted fiber elongation. Overall, the findings of this research provide insights into phenotypic evolution of Gossypium species and regulatory mechanism of nsLTPs during fiber development. HIGHLIGHT A specific group, type XI nsLTPs, was identified with predominant expression in elongating fibers of Gossypium hirsutum based on evolutionary, transcriptional, and functional analyses.